2020
DOI: 10.5206/mase/10739
|View full text |Cite
|
Sign up to set email alerts
|

On mechanisms of trophic cascade caused by anti-predation response in food chain systems

Abstract: Motivated by a recent field study [Nat. Commun. 7(2016), 10698] on the impact of fear of large carnivores on the populations in a cascading ecosystem of food chain type with the large carnivores as the top predator, in this paper we propose two model systems in the form of ordinary differential equations to mechanistically explore the cascade of such a fear effect. The models are of the Lotka-Volterra type, one is three imensional and the other four dimensional. The 3-D model only considers the cost of the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Some different predator-prey systems involving fear effect have been proposed and analyzed, see, for example, Refs. [5,6,9,23,32,33,49]. We describe the impact of fear factors on the food chain model and get the conclusion that fear factors will change the ecosystem from chaotic dynamics to a stable state.…”
Section: Introductionmentioning
confidence: 99%
“…Some different predator-prey systems involving fear effect have been proposed and analyzed, see, for example, Refs. [5,6,9,23,32,33,49]. We describe the impact of fear factors on the food chain model and get the conclusion that fear factors will change the ecosystem from chaotic dynamics to a stable state.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work extends the study of fear effect to food-web systems where more than two trophic levels are incorporated [3,16,17,18,25,26]. In [3], the authors studied a three-species food chain model that includes a bottom prey, a middle predator, and a top predator and showed that the fear effect may drive the transition from chaotic behavior to a stable state for the system.…”
mentioning
confidence: 98%
“…In [3], the authors studied a three-species food chain model that includes a bottom prey, a middle predator, and a top predator and showed that the fear effect may drive the transition from chaotic behavior to a stable state for the system. In [25], Wang and Zou analyzed the cascading effect of the fear from the top predator to the bottom prey where there is either one middle predator or two middle predators at different trophic levels. Other studies include the fear effect in a predator-prey system where there is an alternative food available, a predator-prey community of two predators and one prey, and the digestion delay in the biomass conversation from the prey to the predator [16,17,18,26].…”
mentioning
confidence: 99%